Characterization of nanostructures of TiO2 used as bioreceptor to immobilize laccase enzyme for detection of gallic acid - Ma Guadalupe Garnica-Romo; Mariana Romero-Arcos; Héctor Eduardo Martínez-Flores (Materials Research Express, 2022)
The derived materials obtained from the sol-gel process have been used in various technological applications, such as solar cells, intelligent coatings, catalysis, and, more recently, the fabrication of bioreceptors. The objective of this study was to develop a bioreceptor consisting of a titania-based nanostructure, which was synthesized using the sol-gel method. This nanostructure was immersed in a solution containing laccase and Nafion and integrated into a graphite-based electrode (TiO _2 /NAF/LAC). This device is called a bioreceptor and is used to detect gallic acid. The nanostructure was characterized by x-ray diffraction, Raman spectroscopy, and scanning electron microscopy (SEM). Particle size was measured using a nanosizer. Cyclic voltammetry (CV) tests were performed on a bioreceptor. In this study, the predominant phase of TiO _2 was anatase, and the obtained nanoparticles had an average size of 66 nm. The CV tests of the bioreceptor showed an oxidation response that increased as the concentration of gallic acid in the solution increased, with a detection limit of 0.125 μ M, as well as a wide linear range that varied from 0.125 to 175 μ M and a factor correlation of 0.9968. As a result, it was possible to develop a bioreceptor capable of immobilizing laccase to detect gallic acid.